Reform of state-owned enterprises and privatisation : a dialogue - Sobhan, Rehman; Akash, M. Mokaddem; Akram, Tanweer (CPD monograph ... on governance and development, 1998)
Contributed articles presented at an International Dialogue on Reform of State-owned Enterprises and Privatisation, jointly organised by the Centre for Policy Dialogue and World Bank on 2nd and 3rd November 1996.